THE PERCEPTION OF UNIVERSITAS NEGERI SEMARANG'S JAPA-NESE LANGUAGE EDUCATION STUDENTS BATCH 2018 ON FAC-TORS OF DIFFICULTY IN LEARNING KANJI - Bella Otsa Kristania (Vocational College of Diponegoro University, 2022)
Japanese language learners should find out that Japanese letters consist of hiragana, katakana, kanji, and romaji. However, many people have struggled with learning kanji. It happens because kanji has its reading and writing characteristics. Based on a preliminary study that has been disseminated to Universitas Negeri Semarang's Japanese Language Education students batch 2018, 97.1% agreed that students find it difficult to learn kanji letters. This study was conducted to determine the internal and external factors causing the difficulty of learning kanji from the perceptions of Universitas Negeri Semarang's Japanese Language Education students to batch 2018. In this study, researchers used quantitative descriptive methods through the questionnaire as instrument research, which is in the form of preliminary studies and a questionnaire to obtain research data. Then the researcher uses data analysis techniques in the form of percentages. The results of the research obtained from the questionnaire that the researchers have distributed to students of the class of 2018 of the Japanese Language Education study program, Semarang State University are, internal factors of students' understanding that are different in the meaning of kanji and external factors of the family. These two factors are the factors that students agree with the most as factors causing difficulty learning kanji. The findings indicated that students' various kanji interpretations were the main internal difficulty factor in learning Kanji. The primary external factor that makes learning kanji difficult is family. Most respondents agree that these two factors are the biggest obstacles to learning kanji.